Efektivitas Pengelolaan Data Pegawai Berbasis Website Melalui Sistem Informasi Manajemen Kepegawaian (SIMPEG) Pada Kantor Kementerian Hukum dan Ham Provinsi Sumatera Barat - Erlangga, Ori; Hisham, Muhammad Fazrul; Yunis, Fadhel Fajrin; Hidayat, Rafelia Putri; Hanoselina, Yulia (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
This research aims to analyze the effectiveness of website-based employee data management through the Personnel Management Information System (SIMPEG) at the Office of the Ministry of Law and Human Rights, West Sumatra Province. SIMPEG is a digital system designed to make it easier to manage personnel data in an integrated manner, starting from job history, absences, leave, to performance assessments. This research uses a descriptive method with a qualitative approach to identify the impact of SIMPEG implementation on the speed, accuracy and efficiency of personnel administration. The research results show that SIMPEG has increased the effectiveness of employee data management by reducing data errors, speeding up the decision-making process, and supporting information transparency. However, there are still challenges in the form of limited use of features and disconnection with the National Civil Service Agency (BKN) database, which hinders the synchronization of personnel data nationally. With improvements to system integration and full utilization of SIMPEG features, it is hoped that personnel management at the West Sumatra Ministry of Law and Human Rights can run more optimally